The Intersection of Gender, Culture, and Metacognitive Reading Strategies in Iranian EFL Education: A Mixed-Methods Analysis in Pursuit of Inclusion and Equity - Ghadamgahi, Mahdi; Ghafournia, Narjes (UIR Press, 2024)
In English as a Foreign Language (EFL) education, metacognitive reading strategies (MRS) play a crucial role in learners' reading comprehension. This mixed-methods study investigated MRS among 178 Iranian EFL learners, focusing on gender and sociocultural dimensions. Utilizing an explanatory sequential design, participants—116 females and 62 males—were randomly sampled from two universities in Neyshabur, Iran. For the quantitative phase, a descriptive-correlational design using the Survey of Reading Strategies (SORS) and the TOEFL iBT reading section was employed. Descriptive analysis revealed nuanced differences in the use of MRS among Iranian EFL learners across genders, with an overall higher application by females (M = 3.61) compared to males (M = 3.44). In Support Reading Strategies, females demonstrated a higher application of strategies (M = 3.87) compared to males (M = 3.68). For Problem-Solving Strategies, female learners exhibited more frequent usage (M = 3.72) than their male counterparts (M = 3.46). Additionally, in Global Reading Strategies, there is a slight gender differential, with females showing a higher average score (M = 3.37) as opposed to males (M = 3.26). Independent samples t-tests revealed gender-specific differences in the overall MRS application, particularly in the subcategories of support and problem-solving strategies (p < .05), favoring females. In the qualitative phase, 12 participants were purposively sampled for semi-structured interviews. Thematic analysis identified gender disparities exacerbated particularly by implicit teacher biases and sociocultural factors. These qualitative results corroborated and enriched the quantitative data, especially regarding gender-specific variations in MRS usage.